KONSEP KETUNGGALAN TUHAN DALAM PRAKTIK NAAM JAPNA: KAJIAN ANALISIS PRAKTIK KEAGAMAAN SIKHISME - Firman Nurin Tama; Muhammad Wildan Arif Amrulloh; Abdullah Muslich Rizal Maulana (UIN Sumatera Utara Medan, 2026)
This study examines the relationship between the doctrine of the oneness of God in Sikhism and the spiritual practice of Naam Japna as a primary expression of Sikh religious life. The study addresses the question of how the Sikh concept of monotheism, formulated in the principle of Ik Onkar, extends beyond the theological level and is embodied in everyday spiritual discipline. The study aims to analyze how the repetition of the Divine Name (Waheguru) functions as a medium for internalizing monotheistic consciousness in Sikh religious life. This research employs a qualitative method based on a literature review, utilizing the phenomenology of religion approach and theological-symbolic analysis of primary and secondary Sikh literature. The findings demonstrate that Naam Japna serves as a spiritual mechanism that shifts the orientation of consciousness from egocentrism toward theocentrism through the continuous repetition of the Divine Name. This practice functions not only as devotional meditation but also as an ontological discipline that affirms the presence of the one God in all aspects of life. Furthermore, the internalization of the concept of God through Naam Japna generates ethical implications, particularly an awareness of human equality and a rejection of caste-based social hierarchies. These findings affirm that, in Sikhism, monotheism is not merely doctrinal but is manifested as an existential consciousness that shapes the spirituality, ethics, and collective identity of its adherents.